The Mediating Role of Reputation on Trust, Governance and Sharia Bank Performance - Ambas Hamida; Mursyid Mursyid; Erwin Erwin; Intan Maharani; Anisa Ramadhani; Sulkifra Sulkifra (UIN Siber Syekh Nurjati Cirebon, 2024)
This research aims to analyze the influence of trust and governance on Islamic bank performance which is mediated by corporate reputation. This research uses quantitative methods with data collection techniques through questionnaires with sampling using Accidental Sampling. Data analysis uses Partial Least Square Structual Equation Model (SEM PLS). The research results show that trust has a positive effect on the performance of Islamic banks, but trust does not act as a mediator in the relationship between governance and Islamic bank performance. Furthermore, governance variables have a significant influence on reputation. However, other variables such as governance and reputation have no effect on the performance of Islamic banks. Apart from that, governance on the performance of Islamic banks which is mediated by reputation does not have a significant influence. Overall, trust, governance and reputation play an important role, but to improve the overall performance of Islamic banks requires support from various other factors such as product innovation, operational efficiency, service quality and effective risk management. The results of this research contribute to Sharia Banking to improve company performance through the implementation of Trust, Governance and Corporate Reputation.Keywords: Trust, Governance, Reputation, Company performanceÂ